Literacy and advocacy in adolescent family, gang, school, and juvenile court communities : CRIP 4 life - Smith, Debbie, 1955- (Lawrence Erlbaum Associates, 2006)
Encourages educators and researchers to understand the complexities of adolescent gang members' lives in order to rethink their assumptions about these students in school. This book is useful for education researchers, professionals, and students in the areas of middle/high school education, and alternative community programs.